Pengaruh Brand Image Dan Harga Melalui Minat Beli Terhadap Keputusan Pembelian Produk Fashion Secara Online Di Rawa Lumbu (Studi Pada E-Commerce Zalora) - Tegar Setiawan; Hadita Hadita; Neng Siti Komariah (JURNAL RISET MANAJEMEN DAN EKONOMI (JRIME), 2024)
The purpose of this research is to determine and analyze the influence of brand image and price through purchasing interest on purchasing decisions. The research method used in this research is a quantitative method. Respondents in this research were Zalora consumers in Rawa Lumbu. The population in this study are customers who have purchased fashion products online on Zalora e-commerce. This sampling technique uses the Accidental sampling method which is calculated using the Hair formula. Based on calculations using the Hair formula, it can be concluded that the number of samples obtained was 150 samples. The data used in this research is primary data, namely by distributing questionnaires. The measurement scale used is the Likert scale. The data analysis technique used in this research is structural equation modeling or SEM with the help of SmartPLS 4.0 software. The results of the research show that the brand image variable has a positive and significant effect on purchase interest, the price variable has a positive and significant effect on purchase interest, the purchase interest variable has a positive and significant effect on purchase decisions, the brand image variable has a positive and significant effect on purchase decisions through purchase interest, and The price variable has a positive and significant effect on purchasing decisions through purchase interest.